Pengaruh Komunikasi Interpersonal terhadap Keberhasilan Negosiasi : Survei di Pasar Tradisional Wonogiri - Susila Widhiyanti; Hesti Sadtyadi; Ratna Setyaningsih (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study There is ineffective communication in Wonogiri Market which causes failure in negotiation. Ineffectiveness in negotiation also makes sellers and buyers not have a purchase agreement, sometimes there is a compulsion of sellers so that the goods they sell are immediately sold out so that many other traders compete to provide lower prices. This study aims to determine whether or not there is an influence of communication on the success of negotiations between sellers and buyers in Wonogiri Traditional Market. This study is a quantitative study with a simple linear regression analysis method. This research was conducted in Wonogiri traditional market, on sellers and buyers in March - May 2025. The population of this study was 110 sellers, while the sample used was 84 sellers. The data analysis technique used simple linear regression with the help of the SPSS 25 program. Based on the results of the study and data analysis, it shows that there is an influence of interpersonal communication on the success of negotiations in Wonogiri Traditional Market of 0.581.